Clinical surrogate markers of hypoxemia: Correlation of clinical variables with PaO2/FiO2 ratio - T R Mehta; C T Shah (Journal of Integrated Health Sciences)
Background: Acute respiratory failure is the most common type of organ failure encountered in intensive care unit. PaO2/FiO2 < 300 is diagnostic for acute lung injury, which is measured by arterial blood gas analysis. In our study we aimed to find suitable clinical surrogates of PaO2/FiO2 (P/F). Materials and Methods: This cross sectional study was conducted in intensive care unit of a 1000 bedded hospital. All patients with clinical diagnosis of acute respiratory failure were included in the study. For each patient PaO2 was recorded by obtaining arterial blood gas. Each time P/F ratio was correlated with corresponding clinical signs like single breath count, heart rate, systolic blood pressure, cyanosis, use of accessory muscle etc. Results: Correlation was found between single breath count, heart rate and P/F ratio.